Chemical Composition and Antibacterial Activities of Goniothalamus marcanii Flower Essential Oil - Sakon Monggoot, Patcharee Pripdeevech (Journal of Applied Pharmaceutical Science, 2017)
The essential oil of Goniothalamus marcanii flowers extracted by hydrodistillation was investigated in terms of its chemical composition by gas chromatography-mass spectrometry with their retention indices. The analyses revealed the presence of 116 compounds, representing 93.83% of the essential oil. The major compounds of the oil were caryophyllene oxide, E-caryophyllene, α-humulene, δ-cadinene and linalool. Essential oil of Goniothalamus marcanii flowers were tested in vitro antibacterial activities against six human pathogens including Staphylococcus epidermidis, Staphylococcus aureus, Staphylococcus agalactiae, Proteus mirabilis, Escherichia coli and Salmonella typhimurium by using agar paper disc diffusion assay. Flower oil of Goniothalamus marcanii exhibited broad spectrum antibacterial activities along with their respective minimum inhibitiory concentration values ranging from 15.62 to 1000 µg/mL according to various terpenes and its derivatives.
Keywords: Goniothalamus marcanii, essential oil, GC-MS, antibacterial activity, Minimum inhibitory concentration.